Perilaku Makan Burung Julang Sulawesi (Aceros cassidix) di Kawasan Hutan Maligano Suaka Marga Satwa Buton Utara Sulawesi Tenggara - Andi Firdayanti; Amirullah Amirullah; Muhsin Muhsin (University of Halu Oleo, 2019)
This study aims to know foraging behavior and distribution of peak time of foraging behavior of red knobbed hornbill (Aceros cassidix) In Maligano Wild Life Reserve Of North Buton Southeast Sulawesi. This Study Was Conducted from November-December 2018. Observation was done in the morning and afternoon, for 2 station observations, station I located on the outskirts of Forest while station II is located in the middle of the Forest. Observations of foraging behavior red knobbed hornbill (aceros cassidix) using binoculars and monokuler, as well as documented by using the digital camera. The Method was used to observe foraging behavior of red knobbed hornbill (Aceros cassidix) is a method of observations directly. The distribution of peak time foraging of red knobbed hornbill (Aceros cassidix) seen by the number of the frequency of the emergence of red knobbed hornbill (Aceros cassidix) to do the activity. Observations indicate foraging behavior of red knobbed hornbill (Aceros cassidix) of them is perch and foraging, the move, perched then fly, perch, select the food (gleaning), interesting food (pulling), swallowing food (swallowing), voice, self-cleaning (grooming) and the fly. While the distribution of peak time of red knobbed hornbill raging (aceros cassidix) that is in the afternoon, by the number of individuals that 21 individu that consists of 13 male and 8 females.Keywords : Red knobbed hornbill (Aceros cassidix), foraging, behavior, time ABSTRAKPenelitian ini bertujuan untuk mengetahui perilaku makan serta sebaran waktu puncak makan burung Julang Sulawesi (Aceros cassidix) di Kawasan Hutan Maligano Suaka Marga Satwa Buton Utara Sulawesi Tenggara. Pengamatan perilaku makan dilakukan pada waktu pagi dan sore hari, pada 2 stasiun pengamatan, yaitu stasiun I berada di pinggiran hutan dan stasiun II berada di tengah hutan. Penelitian ini dilaksanakan dari bulan November-Desember 2018. Pengamatan perilaku makan burung Julang Sulawesi (Aceros cassidix) dengan menggunakan teropong binokuler dan monokuler, dokumentasi dengan menggunakan kamera digital. Metode yang digunakan adalah metode pengamatan secara langsung. Sebaran waktu puncak makan burung Julang Sulawesi (Aceros cassidix) dilihat berdasarkan jumlah frekuensi munculnya burung Julang Sulawesi (Aceros cassidix) untuk melakukan aktivitas makan. Hasil pengamatan menunjukkan perilaku dan aktivitas makan burung Julang Sulawesi (Aceros cassidix) diantaranya adalah bertengger dan mencari makan, berpindah tempat, bertengger kemudian terbang, memilih makanan (Gleaning), menarik makanan (Pulling), menelan makanan (Swallowing), bersuara (Voiced), membersihkan diri (Grooming) dan terbang (Flying). Sedangkan sebaran waktu puncak makan burung Julang Sulawesi (Aceros cassidix) yaitu pada sore hari, dengan jumlah individu yaitu 21 ekor yang terdiri dari 13 ekor jantan dan 8 ekor betina.Kata Kunci : Burung Julang Sulawesi (Aceros cassidix), Makan, Perilaku, Waktu